TEKNOLOGI PADA AKUNTANSI MANAJEMEN: MANFAAT ATAU BEBAN? - Febriansyah, Ari; Purba, Daniel Carlos; Muhammad, Sani; Susanto, Sandy (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
The application of technology in management accounting has advantages and disadvantages that create a dilemma for companies in its application. The purpose of this study is to provide an explanation of the benefits and burdens of the application of technology in the field of management accounting, so that later it can be used as a consideration in the application of technology in the field of management accounting. This study uses a qualitative descriptive approach using a literature review sourced from secondary data such as journals, books and relevant online publications which are then analyzed to answer the formulation of research problems. The results of this study indicate that the application of technology in management accounting can improve efficiency, accuracy, security, transparency to strategic decision making, although there are challenges such as costs, data security, and special skills. Therefore, every company needs to evaluate the long-term impact of the application of technology in management accounting for the future and sustainability of the business. Keywords : Management Accounting, Accounting Digitalization, Accounting Technology Transformation